Development of E-Module Based on the Discovery Learning to Improve the Student Creative Thinking Skills - Saryadi, Wahyu; Sulisworo, Dwi (Universitas Muhammadiyah Mataram, 2023)
We are now in an era of very advanced technology. The world is entering the era of the industrial revolution 4.0 which is marked by increased communication, interaction and development of digital systems, artificial intelligence, and virtual. The industrial revolution 4.0 is also shown by the proliferation of computers and recording automation occurring in all fields. With the blurring of boundaries between machines, people and various resources. Through intelligence engineering and the internet of things. However, recently some researchers stated that the use of technology in education has not been maximized. This study aims to analyze the validity, practicality and effectiveness of discovery learning-based e-modules to improve students' creative thinking skills. The method used in this study is Research and Development with the ADDIE type. In the ADDIE technique, there are 5 stages consisting analysis, design, development, implementation, and evaluation. Data collection instruments include validity questionnaires, effectiveness tests and practicality questionnaires. The data analysis techniques used in this study is a qualitative analysis technique consisting of data reduction, data presentation and data inference. The results of the study based on the assessment of material experts obtained an average of 70.00. The results of the media expert's assessment obtained an average of 88.30. Student responses get an average of 80.12. The results of the paired sample test have a significant (2-tailed) value of 0.000. The conclusion of this study is that the developed e-module is valid based on a validity questionnaire, practical based on a practicality questionnaire and effective based on an effectiveness test.